Moral Negotiations and Islamic Family Law in the Digital Age: A Study of the Sugar Daddy Phenomenon Among Muslim Youth - Ahmad; Naharuddin SR; Faisal Nur Shadiq Shabri (Legitima : Jurnal Hukum Keluarga Islam, 2025)
Purpose – This study analyzes the phenomenon of sugar daddies among Muslim youth in the digital age and its implications for the construction and practice of Islamic family law. This study focuses on the increasing tension between transactional intimate relationships, as a consequence of economic inequality and digital platform mediation, and the fundamental principles of marriage in Islam, namely sakinah, mawaddah, and raḥmah, which form the normative basis for family formation in Islam. Method – Qualitative methods were used in this study. Primary data were collected through semi-structured interviews with 15 informants (eight sugar babies, four sugar daddies, and three Islamic law experts) in Indonesia’s Greater Jakarta area. The analysis used the theoretical framework of Islamic law, namely maqāṣid al-sharī‘ah (the objectives of Islamic law) and sadd al-dharī‘ah (prevention of harm). Findings – Thematic analysis shows that sugar dating is triggered by economic pressures (80%) and facilitated by the existence of digital platforms (70%). Analytically, this relationship represents a form of commodification of intimacy that has characteristics similar to practices prohibited in Islam (adultery and contract marriage) because it threatens the institution of marriage itself. The findings also revealed significant religious identity conflicts (feelings of guilt), reinforced power and gender inequalities, and increased health risks for women. These findings confirm that transactional intimate relationships tend to reproduce structural exploitation, with long-term implications for the erosion of fundamental Islamic family values. Research limitations – The small sample size and urban focus limit generalizability, although depth was prioritized for this sensitive topic. Originality/value – This study integrates sociological, digital technology, and Islamic fiqh perspectives by formulating several practical recommendations, including strengthening Sharia-based digital literacy and economic empowerment for youth.